2017
DOI: 10.1002/per.2133
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Neural Correlates of Mentalizing Ability

Abstract: Theory of mind, or mentalizing, defined as the ability to reason about another’s mental states, is a crucial psychological function that is disrupted in some forms of psychopathology, but little is known about how individual differences in this ability relate to personality or brain function. One previous study linked mentalizing ability to individual differences in the personality trait Agreeableness. Agreeableness encompasses two major subdimensions: Compassion reflects tendencies toward empathy, prosocial b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 88 publications
3
46
0
Order By: Relevance
“… 2 In a previously published study using this sample, some facets of Agreeableness were found to be associated with interconnectivity in the DN (Allen, Rueter, Abram, Brown, & DeYoung, 2017). Given the number of tests that would be required, with attendant low statistical power, we did not conduct additional exploratory analysis using the other Big Five traits in the current study. …”
mentioning
confidence: 77%
“… 2 In a previously published study using this sample, some facets of Agreeableness were found to be associated with interconnectivity in the DN (Allen, Rueter, Abram, Brown, & DeYoung, 2017). Given the number of tests that would be required, with attendant low statistical power, we did not conduct additional exploratory analysis using the other Big Five traits in the current study. …”
mentioning
confidence: 77%
“…Furthermore, the DMN is particularly relevant to social cognition as the regions comprising the DMN are also engaged during social and emotional processes (23, 24). It has been argued that DMN RSFC may represent a neuromarker of individual differences in social abilities, predicting mentalizing ability in neurotypicals (25), predicting autistic traits in neurotypicals and people with autism (26), and predicting social network size in macaques (23) and humans (27). While DMN RSFC is an important and flexible tool for investigating social cognition and behavior, it is currently unclear how it relates specifically to the component process of emotion recognition ability.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, other circuits and traits that we did not cover here undoubtedly play a role in how adolescents navigate developmental challenges. For instance, another AMPD trait, Antagonism, has been linked to components of the default mode network implicated in mentalizing abilities [82] and may contribute to a devaluing of stable relationships during adolescence, in favor of short-term rewards (e.g., being more willing to manipulate or exploit a partner for immediate gain). In contrast, high scores on the AMPD’s Negative Affect, coupled with risk-taking, could promote coping strategies meant to gain immediate relief from distress (e.g., self-harm, suicide attempts).…”
Section: Linking Adolescent Neurocognitive Development To Dimensionalmentioning
confidence: 99%